PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 004 DESA TANAH BEKALI KECAMATAN PENGEAN - Rati Hasweni; Lazim N; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrac: This research is motivated by the low results in learning mathematics student SD Negeri 004 Desa Tanah Bekali Kecamatan Pangean with an average grade of 68.42.While the value of the minimum completeness criteria (KKM) Mathematics is 75. Among students 19 people only 8 students who achieved KKM with classicalcompleteness 42.10%.This study is a Classroom Action Research conducted aims to improve mathematics learning outcomes SD Negeri 008 004 Desa Tanah Bekali Kecamatan Pangean the implementation of RealisticMathematics learning approach.Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes.This paper presents the study results of the data obtained from the average of the results of study before action 68.42 increase to 73,68 with a large increased 5,26 (7,69%) in cycle I. In the second cycle increased to 78,43 with a large increased 4,74 (6,43%). In the third cycle increased to 86,84 with a large increased 8,42(10,74%).Teacher activity in cycle I with average persentage of 67.5% in enough categories.in cycle II with average persentage of 82.5% in good categories.in cycle III with average persentage of 92.5% in very good categories. Activity of studens in cycle I with average persentage of 62.5% in enough categories.in cycle II with average persentage of 77.5% in good categories.in cycle III with average persentage of 87.5% in very good categories. Results of the study in Kelas V SD Negeri 004 Desa Tanah Bekali Kecamatan Pangean prove that the application of realistic mathematics learning approach can improve the results of learning mathematics Elementary School fifth grade students SD Negeri 004 Desa Tanah Bekali Kecamatan Pangean.Key Words: Indonesian Realistic Mathematics Education, Learning Outcomes Mathematics